Budaya Politik Masyarakat Urban Kecamatan Ilir Barat 1 Kota Palembang - Muhammad Adi Arfasa; Taufik Akhyar; Yulion Zalpa (Prodi Ilmu Politik FISIP Universitas Islam Negeri Raden Fatah Palembang, 2022)
This research is entitled political culture in urban society in Ilir Barat I sub-district, Palembang city. This study aims to find out and also provide an overview of the results of research that the researcher has done carefully. This study uses a qualitative research method with the type of field research. In the sense that the data obtained by going into the field by collecting data and also information through the results of questions and answers that are used with resource persons. The problem that will be examined in this research is about the form of political culture that occurs in urban communities and also the factors that cause the formation of this political culture. The theory used in this research is the theory of political culture. The results of this study indicate that the political culture that occurs in the Ilir Barat I sub-district, Palembang City has a parochial political culture form caused by several first factors, environmental factors, second social factors, third educational factors, and fourth economic factors. Keywords : Political Culture, Urban Society, Ilir Barat Sub-District 1 Palembang City